2016
DOI: 10.1038/cdd.2016.64
|View full text |Cite
|
Sign up to set email alerts
|

Transthyretin provides trophic support via megalin by promoting neurite outgrowth and neuroprotection in cerebral ischemia

Abstract: Transthyretin (TTR) is a protein whose function has been associated to binding and distribution of thyroid hormones in the body and brain. However, little is known regarding the downstream signaling pathways triggered by wild-type TTR in the CNS either in neuroprotection of cerebral ischemia or in physiological conditions. In this study, we investigated how TTR affects hippocampal neurons in physiologic/pathologic conditions. Recombinant TTR significantly boosted neurite outgrowth in mice hippocampal neurons, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
61
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(67 citation statements)
references
References 59 publications
4
61
0
Order By: Relevance
“…Among the proteins involved in the transport of TH, TTR is synthesized early in development by the liver and the choroid plexus of the brain [9], where it contributes to the transport of T 4 from the blood to the CSF and could have a trophic effect on neurons [10]. In adult mice, TTR is present in the hippocampus, although it is not clear whether it is locally produced by neurons [11, 12] or produced by the choroid plexus and then transported to the hippocampus [9, 13].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the proteins involved in the transport of TH, TTR is synthesized early in development by the liver and the choroid plexus of the brain [9], where it contributes to the transport of T 4 from the blood to the CSF and could have a trophic effect on neurons [10]. In adult mice, TTR is present in the hippocampus, although it is not clear whether it is locally produced by neurons [11, 12] or produced by the choroid plexus and then transported to the hippocampus [9, 13].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, TRHR1 is expressed in granule cells of the dentate gyrus, where it influences neurogenesis [22], and we have recently shown that TRH affects synapse activity [4]. Finally, TTR itself has recently been shown to promote neurite outgrowth and to have neuroprotective properties [23] by interacting with different receptors such as megalin and IGF1R [10] and could therefore act directly to promote plasticity. However, this hypothesis is difficult to test as it is challenging to quantify TTR levels in isolated hippocampus tissue due to recurrent contamination by adherent choroid plexus cells [24].…”
Section: Discussionmentioning
confidence: 99%
“…The gene microarray showed that megalin was also downregulated. Gomes J R et al showed that the interaction of TTR with megalin activates MAP kinase, ERK, Akt and Src, ultimately leading to the upregulation of the CREB transcription factor, as seen for other LRP ligands [34]. TTR is thus a novel megalin ligand with potential importance in T4 transepithelial transport, reinforcing the concept that megalin is a general endocytic receptor for protein in the proximal tubule with a multifaceted role in retaining and capturing vital substances from the tubular fluid after glomerular filtration [35].…”
Section: Discussionmentioning
confidence: 99%
“…TTR stimulation under excitotoxic conditions rescued TTR KO hippocampal neurons in a megalin-dependent manner, which were more sensitive to excitotoxic degeneration than WT neurons [39]. In this process, TTR activates CREB, contributing to changes in the balance between as the receptor involved in the transduction of TTR neuroprotection via megalin in hippocampal neuronal cell culture [23]. TTR interaction with megalin was found to be important determinant for neuronal survival and neurite preservation both in excitotoxic conditions and in a mouse model of permanent middle cerebral artery occlusion (pMCAO).…”
Section: Transthyretin Promotes Neurite Outgrowth In Hippocampal Neurmentioning
confidence: 96%